PENGARUH TIPE MULSA TERHADAP GERMINASI DAN PERTUMBUHAN TANAMAN JAGUNG UMUR MASAK SUSU DI LAHAN PASIR - B. Suwignyo; B. Suhartanto; N. Supartini (Universitas Tribhuwana Tunggadewi, 2012)
The aims of this study was to determine the effect of mulch type on germination and growth of milk stage corn planted at critical sandy land. Plastic mulch and bio mulch (feedstuff used), were used on three beds planted with Pioneer® seed corn. Corn were planted with 25 x 50 cm in sand land Jangkaran Village, Temon, Kulon Progo, Yogyakarta. Litter manure waste was used as basal fertilizer by spreaded over the beds at the level 7.5 t/ha. Corn seed planted on the bed without basal fertilizer and mulch as a control. Chemical fertilizers in the form of urea and SP-36 is given in equal amounts and the corresponding frequency written on the label. Growth characteristic was measured every week. The study is used completely randomized design (CRD) and the data were analyzed by ANOVA with SPSS advanced analysis of LSD. Utilization of mulch has significant effect on the growth of corn plants compared to corn without mulch; bio mulch has the highest effect. Mulch has no significant effect to the germination. Utilization of mulch (both plastic and bio) in the critical sandy land are very recommended, while the bio mulch recommend to production and economic value